2
$\begingroup$

This is probably a silly question and maybe in the end the answer is trivial but I can't see it.

The problem is the following.

Let $M$ be a Riemannian manifold, $\gamma \colon[0,l]\to M$ be a geodesic and let $X \in \mathcal{X}(M)$, where $\mathcal{X}(M)$ is the space of all the smooth vector fields on $M$. Assume that $X(\gamma(0)) = 0$. I want to show $$ \nabla_{\gamma'}(R(\gamma',X)\gamma')(0) = (R(\gamma', X')\gamma')(0), $$ where $X' = \frac{DX}{dt}$ and $R$ is the Riemann curvature.

In the book there is the following hint.

Hint: Let $R$ be the curvature tensor. Observe that, for all $Z \in \mathcal{X}(M)$, and $t=0$,

\begin{align} 0 &= (\nabla_{\gamma'}R)(\gamma', X, \gamma',Z) \\ &=\frac{d}{dt}\langle R(\gamma',X)\gamma', Z \rangle - \langle R(\gamma', X')\gamma',Z\rangle - \langle R(\gamma',X)\gamma', Z'\rangle \\ &=\langle\nabla_{\gamma'}(R(\gamma',X)\gamma'),Z\rangle - \langle R(\gamma',X') \gamma', Z \rangle. \end{align}

The only thing I can't understand is the first equality. How do we know that $(\nabla_{\gamma'}R)(\gamma', X, \gamma',Z) = 0$ ?

$\endgroup$
4
$\begingroup$

I asked this question also in the forum MathOverflow even though this question is so basic. Indeed somone solved my problem almost immediately in the comments. I write the answer here because maybe can be useful to someone in a future.

The answer (as I espected) was obvious and I had this problem just because tensors are a new thing for me.

The object $\nabla_{\gamma'}R$ is a $4$-tensor and since $X(\gamma(0))=0$, then it's clear that $(\nabla_{\gamma'}R)(\gamma', X, \gamma', Z)=0$ in $t=0$, because $$(\nabla_{\gamma'}R)(\gamma', X, \gamma', Z)|_{t=0}= (\nabla_{\gamma'}R)(\gamma'(0), X(\gamma(0)), \gamma'(0), Z(\gamma(0))) = (\nabla_{\gamma'}R)(\gamma'(0), 0, \gamma'(0), Z(\gamma(0))) = 0.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.